Reassessment of radiation correlations & long-term collectable energy of principal solar collector types and proposal of a generalized procedure of obtaining utilizability correlations - Attalage, Rahula Anura; Reddy, T. A.; Prida Wibulswas; Lasnier, France; Deutsher Akademischer Austa uschidienst (DAAD) (Bangkok : Asian Institute of Technology, 1986)
There are various empirical correlations available for estimating different radiation components. These have been developed using a finite data base of limit e d number of locations. Among them four widely used empirical correlations are selected, and analyzed in order to see the prediction accuracy of these correlations when applied to arbitrary locations. The hourly data of 26 locations (data of a typical meteorological year, per location) and hourly data of 4 Australian locations (data of 10 years per location, with some locations containing a typical meteorological year) have been selected for this analysis. The estimation of the prediction accuracy is based on the statistical estimators of Mean bias error & Root mean square error, and on the development of the probability density curves, in terms of relative and absolute errors. The effect of the clearness index in also emphasized in the analysis. Finally the analysis results in a comparison of the prediction accuracies of different correlations, and the limiting range within which the error values reside for a particular correlation. The second aspect of this study deals with yearly collectable energy of principal solar collector type s . Gordon & Rahl ' s yearly collectable energy correlations are reassessed and validated against the results of hour by hour simulated actual data, of US and Australian location respectively. The estimation of the prediction accuracy is based on the same statistical estimators as stated earlier and on the development of probability density curves, in terms of relative errors. Two n ew correlations are developed for estimating yearly collectable energy for flat plate collector tracking about north -south polar axis and two -axes. Validation and reassessment of the proposed correlations s how that, the correlation for two - axes case seems as good a s Gordon & Rahl ' s correlations. The effect of shading and the use of anis tropic sky model on the predictions have also been analyzed. The final section of this study aims at proposing a generalized procedure, in order to obtain hourly and daily utilizability functions on any time scale, starting from a location specific parameter, the clearness index. The proposed procedure in the study deals only with the case of flat plate solar collector deployed at any tilt, facing due south. Starting with the location specific monthly mean daily clearness index on a horizontal surface, monthly- hourly, monthly- daily and yearly-daily utilizability functions for flat plate, facing due south at any tilt are derived. The obtained utilizability functions are validated with actual data and compared with other empirical correlations of utilizability. Finally the extension of this proposed procedure on to concentrating collectors is also suggested
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Solar collectors